Perception and prejudice about organ donation among medical students in a tertiary healthcare, Mysuru - S., Rashmi; M. R., Narayana Murthy (International Journal Of Community Medicine And Public Health, 2019)
Background: Today, increase in deaths due to organ failure can be avoided if organ donors are available. Many states in India adopted the transplantation of human organs act and enthusiastic medical professionals and philanthropists joined hands to move the matter further forward. Lack of awareness about organ donation has been noted among the general public including medical professionals. Awareness can be promoted through medical students to bridge the gap of knowledge about organ donation and they can carry the message to the community. Hence an attempt has been made to probe this issue with objective to assess the perception and prejudice about organ donation among medical students. Methods: This cross-sectional study was conducted among medical students in a tertiary healthcare centre, Mysuru. A total of 201 students from 1st and 3rd term, consenting to participate were included in the study. A semi-structured self-administered questionnaire was used to collect data and was analysed using SPSS 22 version. Results: Knowledge about brain death was 73.1%, transplant of harvested organs was 59%, compatibility tests were 89% and organs donated by live donors were 89.6% for kidneys and 66.7% for cornea in cadaver donors. Regarding legal issues 73% knew that organ selling is criminal offence. 90% supported organ donation and related to prejudice 53% agreed that there are no religious constraints to donate organs. Conclusions: Knowledge and awareness regarding procedure, pre-requisites and legal issues related to organ donation needs to be improved among the medical students.